Empirical estimates for the Brazilian total imports equation using quarterly national accounts data (1996-2010) - Raphael Rocha Gouvêa; Bernardo Patta Schettini (EconomiA, 2015)
This paper presents econometric estimates for the Brazilian aggregate imports over the period 1996–2010. To the best of our knowledge, this is the first paper that uses the Brazilian quarterly national accounts with this goal in mind. Besides estimating a demand equation (canonical model), as it is usual in the literature, we also explore the co-movements among total imports, gross fixed capital formation and household consumption (alternative model). The results underscore the role played by domestic income, which is the main determinant of total imports. The limited domestic supply of capital goods makes the allocation of domestic income also relevant to the imports dynamics. It should be noted, however, that this specification needs a better theoretical grounding. Evidence of nonlinearities has been found by different estimation techniques. Unfortunately its precise characterization turns out to be difficult due to the diversity of the results obtained. The out-of-sample assessment (one-step-ahead forecast) shows a good performance of the long-run vectors of the alternative models in predicting aggregate imports, meanwhile the best performance is obtained by the error correction representations of the canonical model. We believe those differences emerge from the different speeds of adjustment toward the long-run solutions. – – O presente artigo apresenta estimativas econométricas das importaç\~oes agregadas brasileiras. A primeira inovaç\~ao reside na utilizaç\~ao dos dados de importaç\~oes das contas nacionais trimestrais. A segunda contribuiç\~ao se refere aos modelos empíricos, pois, além da equaç\~ao de demanda (modelo canônico), exploramos o comovimento das importaç\~oes com a formaç\~ao bruta de capital fixo, além do consumo das famílias (alternativo). Em terceiro lugar, a instabilidade dos parâmetros foi examinada por diferentes técnicas. Em relaç\~ao aos resultados, vale destacar o papel da renda interna, que é o principal determinante das importaç\~oes. A limitada oferta doméstica de bens de capital faz com que a alocaç\~ao da renda interna seja relevante, cabendo notar que essa especificaç\~ao necessita de uma fundamentaç\~ao teórica melhor. Embora tenham sido encontradas evidências de n\~ao linearidades, a diversidade de resultados torna difícil sua caracterizaç\~ao exata. Na avaliaç\~ao fora da amostra (previs\~oes um passo à frente), os vetores de longo prazo apresentaram bom desempenho para o modelo alternativo, enquanto as representaç\~oes de correç\~ao de erros do modelo canônico obtiveram os melhores resultados, estando essa diferença possivelmente relacionada às distintas velocidades de ajustamento na direç\~ao da soluç\~ao de longo prazo.
Keywords: C22; C52; F1; F17; 330; Quarterly Brazilian imports; Cointegration models with structural breaks; Markov-switching models; State-space models